Pendidikan Karakter Menurut K.H. Hasyim Asy’ari dalam Kitab Adâb al-‘Âlim wa al-Muta‘allim - Sholikah, Sholikah (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The article deals with K.H. Hasyim Asy’ari’s thought of character education. The result of the study indicates that according to K.H. Hasyim Asy’ari the characters of teachers and students in his work Adab al-‘Âlim wa al-Muta’allim can be classified into three parts, are mentality or character, which should be possessed by teachers and learners: attempts to be done in order to become characterized teachers and learners, and: teaching strategies employed by educators and learning strategies used by learners. These three parts have compatible indicators with the competence of educators stated in UU Sisdiknas (The Legislation of National Educational System) year 2003 along with 18 values of character promulgated by Pusat Kurikulum Pengembangan dan Pendidikan Budaya dan Karakter Bangsa. Moreover, according to K.H. Hasyim Asy’ari, the relevance of character education with the context of character education in Indonesia consists of a number of character education elements, namely the meaning and goal of character education, the values of character for both teachers and students, the rationale of character education, the method of character education, the media of character education, and the evaluation of character education